ANALISIS KEMAMPUAN MEMBACA SISWA KELAS I A SD NEGERI 1 MANGARAN TAHUN AJARAN 2022/2023 - Puspitaningtyas, Amalia Risqi; Rofek, Aenor; Fernanda, Pramita Tri; Jamila, Nur; Prabu, R. Moh Abdul Qodir (Dharmas Education Journal (DE_Journal), 2023)
Students still have difficulty in reading. Students who experience these difficulties will have difficulty understanding the material. This study aims to determine reading ability by using interview, observation, and documentation techniques. The instruments used are interview guides, observation sheets, and documentation. The main source in this study was class I A students at SD Negeri 1 Mangaran and the second source was the teaching teacher or homeroom teacher. Based on the data obtained, it is known that reading difficulties are influenced by a lack of guidance and attention from parents and teachers which have an impact on student learning outcomes. The results of this study indicate that providing special guidance to students who have reading difficulties will have an impact on reading skills and improve student learning outcomes. There are 4 criteria for assessing reading ability, namely the first is fluency in reading, accuracy in reading, correct pronunciation, and intonation. So, it can be concluded that there are seven students who are fluent in reading sentences or are good enough, seven students are very good at reading out of a total of 19 students who entered. We can also conclude that the reading ability of class I A at SD Negeri 1 Mangaran is still categorized as quite good, because the number of students who can read fluently has not reached 80%.